Implementasi Metode Lempel-Ziv-Welch pada Kompresi File Teks - Setiawan, Muhammad Charis; Yuliastuti, Gusti Eka; Rachman, Andy (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2023)
The increasing use of digital data in this era goes along with the increasing need to store data on storage media. As a result, data security becomes important when using the internet, especially websites, because they also have security threats such as attacks on URLs that can penetrate databases. In response to problems of increasing data and URL security, compression is necessary for data and encryption is beneficial for URL security. This study employed the half-byte compression method and cipher block chaining encryption. The data used for compression comprised txt, docx, and doc files, while the encrypted URL used the ID of the file. The results of the average value of compression testing obtained the highest compression ratios for.txt files (1.150), docx files (120.469), and doc files (47.622). Meanwhile, the results of encryption testing obtained an average encryption execution time of 0.0000466347 seconds. The attempt to penetrate the database through SQL injection failed. In conclusion, the best average occurred in a.docx file because docx/doc files only compress text without images, making the half-byte method applied by researchers only suitable for files containing text. Encryption was able to protect against SQL injection attacks, and the execution time was quite good, under 1 second.